(untitled) (Repertorio Científico, 2022)
The production of new varieties for agriculture is very important to be more profitable and productive, in addition to being able to adapt to climate change. For their part, blocky varieties are growing in consumer demand in Costa Rica. The objective of this research was to carry out the evaluation of F1 hybrids of C.annum focused on obtaining local seed of varieties such as "Bell Pepper or Blocky", yellow, red and orange; also elucidate some inheritance traits. Also evaluate commercial varieties and progenies obtained by self-pollination in commercial varieties. A field evaluation of the F1 hybrids was carried out with a Latin square experimental design, with 4 blocks and 4 repetitions per evaluated progeny, coming from the initial crosses. To analyze the data, an ANOVA was performed with a confidence level of p <0.05%. In addition to the hybrids, the commercial varieties and their respective self-pollinations were evaluated. Regarding results, the variables of plant height, length and diameter of the fruit did not show significance, in the F1 hybrids (p <0.05), except for the variable average fruit weight, in which there were significant differences (p> 0.05), the above indicates uniformity of the hybrids and the use of pure lines as parents. In relation to the inheritance of the characters, it was observed 100% dominance of the red color in the shell and square shape in the fruit for the three hybrids according to Mendel’s laws for uniformity.For the purposes of the research, the commercial varieties (Nathalie, Bell Pepper Red, Orange and Yellow) were also evaluated and self-pollinations were made in each one measuring the same variables as in the F1, this was done with the intention of seeing the inheritance of some characters and see if the seed of each commercial variety was a pure line or a hybrid. Among the most outstanding results, it is pointed out that the variety of chili type "lamuyo" Nathalie, Bell Pepper Red, Orange and Yellow are pure lines and not hybrids, since there was no segregation and what was obtained was identical to the commercial lines, on the other hand , Nathalie, being self-pollinated, was the variety that obtained the most fruits, in relation to all the varieties compared, which can be explained from the physiological point of view by the size of the fruits and the thickness of the peel in relation to the varieties of type Bell Pepper. Regarding the F1 and the production obtained, all obtained positive results according to the heterosis calculation method. The hybrid encoded as (T) x BA, produced 0.98 fruit units more than its parents with a percentage of heterosis of 32.03%, followed by the hybrid (T) x BR with a percentage of heterosis of 4% and finally the hybrid (T) x BN with a percentage of 3.74%. Finally, uniform hybrids were obtained in all variables except fruit weight. Red is dominant over yellow and orange. It was found that the parents used and the commercial varieties were pure lines.